The non-Israelite nations in the Book of the Twelve : thematic coherence and the diachronic-synchronic relationship in the minor prophets - Timmer, Daniel C. (Biblical Interpretation Series, 2015)
In The Non-Israelite Nations in the Book of the Twelve Daniel Timmer offers the first comprehensive survey of the 'nations' in the Minor Prophets. The study approaches this important but highly diverse theme through the lens of conceptual coherence and demonstrates the interrelation of synchronic/holistic and diachronic/compositional approaches. After exploring the theme in each of the individual books of the Twelve and noting the varying degrees of coherence evident in each case, Timmer brings his findings to bear on contemporary understandings of the Twelve as a collection, arguing for the theme's coherence across the collection on the basis of each book's unique treatment of the nations.